2017
DOI: 10.1080/20786190.2017.1396790
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unintended pregnancy among women attending a public health facility in KwaZulu-Natal, South Africa

Abstract: Background: Across the globe a large proportion of pregnancies have been reported as unintended. There are no available reports from South Africa concerning the prevalence of unintended pregnancies. This study explored the prevalence of unintended pregnancies among South African women attending a public primary health care (PHC) clinic in KwaZulu-Natal (KZN), South Africa. It also investigated the relationship between demographic factors, contraceptive use, substance abuse and unintended pregnancy in this sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
41
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
13
41
3
1
Order By: Relevance
“…The prevalence of the unintended pregnancy observed in this study is in agreement with the ones found by studies conducted at Debre Markos (32.9%) and Addis Ababa (36.4%) [11][12][13][14]. But it is lower than the magnitudes reported from South Africa (64%), Nepal (54.5%), and Arsi zone (41%) [11][12][13]. This might be due to the difference in sample size, sociocultural characteristics, and health coverage of the study area, as well as the difference in the availability and accessibility of services (like access to modern contraceptives) for maternal health service in the countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of the unintended pregnancy observed in this study is in agreement with the ones found by studies conducted at Debre Markos (32.9%) and Addis Ababa (36.4%) [11][12][13][14]. But it is lower than the magnitudes reported from South Africa (64%), Nepal (54.5%), and Arsi zone (41%) [11][12][13]. This might be due to the difference in sample size, sociocultural characteristics, and health coverage of the study area, as well as the difference in the availability and accessibility of services (like access to modern contraceptives) for maternal health service in the countries.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of the unintended pregnancy observed in this study is in agreement with the ones found by studies conducted at Debre Markos (32.9%) and Addis Ababa (36.4%) [11][12][13][14]. But it is lower than the magnitudes reported from South Africa (64%), Nepal (54.5%), and Arsi zone (41%) [11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Efikasi diri ibu terkait kesehatan cenderung lebih rendah pada orangtua yang berpenghasilan rendah (Holland et al, 2011). Pendapatan keluarga rendah memiliki tingkat kehamilan yang tidak diinginkan lebih tinggi daripada keluarga yang memiliki pendapatan tinggi karena ibu yang memiliki pendapatan rendah jarang menggunakan alat kontrasepsi dan mengalami tingkat kegagalan kontrasepsi yang lebih tinggi (Haffejee et al, 2017). Orangtua yang memiliki pendapatan rendah akan mengkhawatirkan biaya yang dikeluarkan untuk makanan, kesehatan, pakaian dan biaya lainnya yang cukup besar.…”
Section: Pengaruh Tingkat Pendidikan Ter-unclassified
“…The proportion of unintended pregnancy was found to be specifically higher among younger women (aged 15-19 years old) compared to older women (Ikamari et al 2013). A pregnancy can be unintended for many reasons such as believing to have too many children already, no desire to have children at the moment, not having the financial resources available to support a new child, being in school, being unmarried, or the pregnancy might have been a result of incorrectly using or lack of access to contraceptives (Singh et al 2006;Haffejee et al 2018).…”
Section: Introductionmentioning
confidence: 99%